PERENCANAAN STRATEGIS PROGRAM STUDI TEKNIK INFORMATIKA PADA AMIK AKMI BATURAJA BERBASIS INFORMASI - Satria Novari (Jurnal Informatika dan Komputer (JIK), 2019)
Informatics Engineering is one of the study programs at AMIK AKMI Baturaja. The informatics engineering study program must have a valid framework for developing information and documentation systems. Therefore, strategic planning in this study program must have an integrated information system that needs to be prepared and prepared carefully for an educational institution such as an informatics engineering study program.This paper will present information systems strategic planning in the Informatics Engineering study program to lead to superior technology-based study programs. At this researcher the author will use SWOT analysis, including strengths, Opportunities, weaknesses, and Threats. By using SWOT analysis it is expected that this will be able to overcome by dividing each problem that arises by finding the best solution.